Measurement of e-school User Experience, Does it Support Blended Learning during the Covid-19 Pandemic ? : (Case Studies at Three Parent Schools LPKA Class I Palembang) - Febrianty, Febrianty; Hadiwijaya, Hendra; Octafian, D. Tri (Politeknik Ganesha Medan, 2021)
This study aims to measure the User Experience of e-school in supporting blended learning during the Covid-19 Pandemic. The object of this research is the parent school of LPKA Class I Palembang, namely: SDN 25, SMPN 22, and SMAN 11 Palembang. Because of this, all of the parent schools implemented an e-school web system adapted from the LPKA Class I Palembang filial e-school. The method used in this study was UEQ which was introduced by (Schrepp, 2018). The results of UEQ measurements on parent-school students show that: a). web e-school SDN 25 Palembang, on the scale of attractiveness, clarity, and accuracy are categorized as